The Analysis of Health Professional’s Knowledge and Attitudes Related to The Implementation of Pharmacovigilance in Pharmaceutical Service Facilities - Ema Nillafita Kusuma; Aas Sa’adah; Dian Farida Ismyama (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
In May 2024, the Indonesia Food and Drug Authority received less than 10,000 reports of adverse events (AEs), or around 3,773 reports. A lack of understanding of the urgency of pharmacovigilance results in a small number of reports compared to the population. This potentially poses unidentified safety risks, reduces quality of life and increases the cost of therapy. This research aims to describe and provide information related to the knowledge and attitudes of healthcare professionals in responding to safety information or AEs, as well as explain the types of drugs and side effects seen by healthcare professionals. This is a non-experimental prospective study and uses a descriptive-analytic research design. The data was taken from August to October 2024, by using a structured questionnaire. The respondents of this study are healthcare professionals, who are 72% females and 28% male. Almost 54% have received and found AEs. The most frequently reported AEs were related to Antibiotics, Analgesics, Anticonvulsants, Anti-Tuberculosis, and Bronchodilators. Based on Pearson Correlation Analysis, there was a moderately significant relationship between knowledge and attitudes (p<0.05). It can be concluded that the number of AEs reported will be increased if there is an increase in healthcare professional knowledge continuously.